Phenolic Contents and Antioxidant Activity of Extracts of Selected Fresh and Dried Herbal Materials - Mariola Kozłowska; Iwona Ścibisz; Jarosław Przybył; Małgorzata Ziarno; Anna Żbikowska; Ewa Majewska (Polish Journal of Food and Nutrition Sciences)
Total phenolic content (TPC) and phenolic profiles of extracts of the aerial parts of coriander ( Coriandrum sativum L.), lovage ( Levisticum officinale Koch.), and tarragon ( Artemisia dracunculus L.), and leaves of Indian borage ( Plectranthus amboinicus ) have been investigated. The extracts were prepared using 70% ( v/v ) ethanol and fresh or air-dried herbal material. Besides phenolic composition, DPPH • and ABTS •+ scavenging activity, and ferric-reducing antioxidant power (FRAP) were determined. The extracts from dried herbal materials exhibited higher TPC and more potent antioxidant activity than those from fresh counterparts. The highest TPC (146.77 g GAE/kg extract) and antioxidant activity (0.491, 0.643, and 0.396 mol TE/kg extract in DPPH, ABTS, and FRAP assays, respectively) were detected for the extract from dried leaves of Indian borage, while the lowest values were determined for the extract from fresh aerial parts of coriander. Five phenolic acids (rosmarinic, chlorogenic, caffeic, ferulic, and neochlorogenic acids) and four flavonoids ((+)-catechin, rutin, hyperoside, and astragalin) were identified in the samples. Only caffeic acid was present in all extracts. Its content in the extracts of dried tarragon and Indian borage was lower than in those of the fresh material. A significant correlation was found between antioxidant activity and the content of phenolic acids. Rutin was found to be the major flavonoid in most extracts. Based on the present study results, the possibility of using the extracts obtained from both fresh and air-dried herbs as potential components for functional food formulation can be considered in the future.